2004
DOI: 10.1097/01.brs.0000144354.36449.2f
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Venous Plexus Enlargements Presenting With Radiculopathy and Back Pain in Patients With Inferior Vena Cava Obstruction or Occlusion

Abstract: The authors believe that epidural venous engorgement should be considered when the symptoms of patients with deep venous and inferior vena cava thrombosis are accompanied by radicular and/or back pain, because pathologic processes compressing a nerve root can cause pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 8 publications
2
101
0
1
Order By: Relevance
“…9 In these patients, collateral vein engorgement due to IVC occlusion may extend to the epidural or interforaminal space; this may eventually lead to symptoms that are suggestive of disc herniation or foraminal stenosis. 10 Bozkurt et al 1 reported a case of radicular and low-back pain secondary to IVC stenosis in a patient with Budd-Chiari syndrome that was successfully treated with an endovascular procedure. To our knowledge, ours is the second reported case involving epidural venous engorgement due to Budd-Chiari syndrome Type I, which has occlusion of hepatic veins by thrombosis, not compression of an outside structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In these patients, collateral vein engorgement due to IVC occlusion may extend to the epidural or interforaminal space; this may eventually lead to symptoms that are suggestive of disc herniation or foraminal stenosis. 10 Bozkurt et al 1 reported a case of radicular and low-back pain secondary to IVC stenosis in a patient with Budd-Chiari syndrome that was successfully treated with an endovascular procedure. To our knowledge, ours is the second reported case involving epidural venous engorgement due to Budd-Chiari syndrome Type I, which has occlusion of hepatic veins by thrombosis, not compression of an outside structure.…”
Section: Discussionmentioning
confidence: 99%
“…2 Patients with these problems commonly complain of symptoms suggestive of lumbar disc herniation or spinal stenosis. 10 Most of these patients present with low-back pain, radicular pain, or neurogenic claudication, but they rarely exhibit serious symptoms such as neurological deficit or cauda equina syndrome. 8 Lower-extremity weakness and voiding difficulty are generally considered to indicate serious complications due to thoracolumbar spinal diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epidural venous engorgement should be considered when the symptoms of patients with deep venous and inferior vena cava thrombosis are accompanied by radicular and/or back pain, because pathologic processes compressing a nerve root can cause pain (5). In some cases, as we have observed in a pregnant woman, thrombosis of inferior vena cava can extend to the renal vein giving rise to a more complex set of symptoms (6).…”
Section: Case Reportmentioning
confidence: 99%
“…In the 1960s, 4.4% of lesions preoperatively diagnosed as lumbar disk hernia were believed to be vascular abnormalities. 9) However, computed tomography (CT) and magnetic resonance (MR) imaging have reduced the incidence of confirmed epidural varices to 0.067-1.2%, 15,17,19) although a rate of approximately 5% has been reported. 10) Only 1 of 823 patients (0.12%) subjected to lumbar surgery at our institute between 1994 and 2006 was confirmed to have lumbar epidural varix.…”
Section: Introductionmentioning
confidence: 99%